Does ESG Performance Enhance Financial Outcomes? Empirical Evidence from Indian FMCG Sector - Sitola, Dipti; Choudhury, Smritishikha; Senapati, Chayanika; Bhattacharyya, Archana (International Journal of Economics and Financial Issues, 2025)
This study aims to evaluate the current status of Environmental, Social, and Governance (ESG) performance within the Indian Fast-Moving Consumer Goods (FMCG) sector and to empirically investigate the impact of both aggregated and disaggregated ESG dimensions on firms’ financial performance (FP). The research adopts a cross-sectional analytical framework based on secondary data from a sample of 80 Indian FMCG companies for the financial year 2024–25. ESG performance indicators were sourced from the Credit Rating Information Services of India Limited (CRISIL), while data pertaining to financial performance metrics were obtained from annual reports of the concerned companies. Descriptive statistics were utilized to assess the current ESG landscape in this sector. To examine the relationship between ESG and FP, Ordinary Least Squares (OLS) regression models were employed, with ESG (overall and individual dimensions) as independent variables and financial performance, proxied by Return on Net Worth (RONW), as dependent variables. The findings reveal that among the three ESG pillars, the Indian FMCG sector places the greatest emphasis on governance, followed by social and environmental considerations, where the environmental dimension receives the least attention. The regression analysis shows that RONW is significantly and positively influenced by environmental and governance performance, as well as overall ESG scores. However, the social dimension exhibits an insignificant impact on both financial performance indicators. These results suggest a partial integration of ESG principles, with firms deriving more tangible financial benefits from governance and environmental initiatives than from social initiatives. This study contributes to the growing ESG-finance literature by offering fresh insights into the Indian FMCG sector-an under-explored domain in emerging economies. It highlights the different effects of disaggregated ESG dimensions on firm performance and provides actionable implications for managers, investors, and policymakers seeking to align sustainability efforts with financial objectives.